2004
DOI: 10.1111/j.1875-595x.2004.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride mouth rinsing proficiency of Japanese preschool-aged children

Abstract: That Japanese preschoolaged children could perform fluoride mouth rinsing safely and efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…For these reasons, it is estimated that fluoride mouth-rinsing is being performed in groups and at home by about 100 million people throughout the world19,20. In particular, reports have claimed that fluoride mouth-rinsing for preschool children is very safe in Japan compared with Western countries1–6, and it is recommended that children begin fluoride mouth-rinsing either through the S-FMR or at home, from age 4 or 5 years5,6. A WHO website (WHO Bank of Ideas) also states that the S-FMR performed at preschools is extremely beneficial for countries such as Japan that do not fluoridate the water21.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For these reasons, it is estimated that fluoride mouth-rinsing is being performed in groups and at home by about 100 million people throughout the world19,20. In particular, reports have claimed that fluoride mouth-rinsing for preschool children is very safe in Japan compared with Western countries1–6, and it is recommended that children begin fluoride mouth-rinsing either through the S-FMR or at home, from age 4 or 5 years5,6. A WHO website (WHO Bank of Ideas) also states that the S-FMR performed at preschools is extremely beneficial for countries such as Japan that do not fluoridate the water21.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation rates and participation rates are even lower in elementary and junior high schools when compared with preschools and kindergartens. One factor accounting for the higher implementation rate in preschools and kindergartens may be that it is being pursued on the basis of safety1–6. While it is easy for preschools and kindergartens to implement the S-FMR, increasing implementation rates at elementary and higher level schools remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the collective perceptions of dental health experts were that the successful development and implementation of fluoride mouth rinsing programs should recognize the fundamental role of the political process (will) at the municipal level which acts though the provision of reliable scientific information about fluoride applications. Since the safety and effectiveness of the use of fluorides, including fluoride mouth rinsing programs has been proved in Japan (Kobayashi et al, 1995, Sakuma et al, 2004, the power to enforce actions through the political process seems to be identified as the most important factor to develop programs. The criterion "expertise on dental health" was assigned low weight therefore illustrating the lack of influence at the municipal level of such expertise.…”
Section: Pathway Determination -Municipal Decisionmaking and Fluoridementioning
confidence: 99%